A retrospective review of ranson score versus apache-ii score in predicting outcomes of acute pancreatitis in Hospital Universiti Sains Malaysia - Mokhter, Wan Muhamad Mokhzani Wan Muhamad (2013)
Acute pancreatitis is a common and potentially lethal inflammatory process with a highly variable clinical course. Persistent organ failure develops in 10-20% of patients, with mortality reaching 30% in this subgroup. It is therefore important to identify patients with acute pancreatitis who are at risk for developing persistent organ failure early in the course of the disease. Ranson score and APACHE-II system are two of the many scoring systems utilized for predicting acute pancreatitis with adverse outcomes. The present study is aimed at assessing both scoring system for its sensitivity, specificity, PPV, NPV and comparing them using the relevant statistical tools to assess and determine which system is better at predicting outcomes of patients with acute pancreatitis presenting to Hospital Universiti Sains Malaysia between 2007 to 2011. Case notes of 156 patients with acute pancreatitis were reviewed retrospectively, Ranson score and APACHE-II score are assigned according to the relevant parameters and outcome is documented for each case. Ranson score is categorically assigned as mild (score less than 3) or severe (score equal to or more than 3) and APACHE-II score as mild (score less than 10) or severe (score equal to or more thanlO). Outcome is also categorically assigned as good (patient discharged from hospital) or poor (patient requires ICU admission, intervention either surgical or radiological and death). Chi-squared test was used to determine association of each test with outcomes and kappa-test was applied to determine strength of relationship for each test with outcomes of acute pancreatitis. Both Ranson score equal to or more than 3 and APACHE-II score equal to or more than 10 are associated with poor outcome of acute pancreatitis in the study cohort (p<0.01). The sensitivity and specificity for Ranson score or equal to or more than 3 is 94.1% and 68.3% respectively (PPV 26.7%. NPV 99.0%). The sensitivity and specificity for APACHE-II score equal to or more than 10 is 70.6% and 90.6% respectively (PPV 48.0%, NPV 96.2%). The kappa value for Ranson score is 0.30 (fair relationship) and kappa value for APACHE-II score is 0.51 (moderate relationship).